Applied Ergonomic Methodology for Current Engineering Practice - Fiserova, Svetla (Communications - Scientific letters of the University of Zilina, 2011)
A human factor is part and parcel of each work system. The current ergonomic methodology enables applications related to the evaluation and design of work systems that take into account both basic aspects of each work system, namely the technical and human aspects. The contribution focuses on the hierarchical classification of methods intended for the use in work systems under the conditions of current engineering practice.